Opinion: Can governance reforms like Brazil’s get us to net-zero? - Verchot, Louis V.; Castro-Nuñez, Augusto Carlos (CGIAR System Organization, 2022)
Can governance reforms like Brazil’s get us to net-zero? One narrative present among climate change discussions is that reducing agricultural greenhouse gas, or GHG, emissions would compromise food security and the availability of food in the global south. We agree that reducing GHG emissions comes with trade-offs, but this does not mean we should abandon efforts toward climate change mitigation in agriculture and forestry, which the Paris Agreement champions.